The looking machine essays on cinema, anthropology and documentary filmmaking - MacDougall, David (Manchester, [England] Manchester University Press, 2019)
This new collection of essays presents the latest thoughts of one of the world's leading ethnographic filmmakers and writers on cinema. It will provide essential reading for students in cinema studies, filmmaking, and visual anthropology. The dozen wide-ranging essays give unique insights into the history of documentary, how films evoke space, time and physical sensations, and the intellectual and emotional links between filmmakers and their subjects. In an era of reality television, historical re-enactments, and designer packaging, MacDougall defends the principles that inspired the earliest practitioners of documentary cinema. He urges us to consider how the form can more accurately reflect the realities of our everyday lives. Building on his own practice in filmmaking, he argues that this means resisting the pressures for self-censorship and the inherent ethnocentrism of our own society and those we film.
Introduction -- Part I. Filmmaking as practice. Dislocation as method -- Looking with a camera -- Camera, mind and eye -- Environments of childhood -- Part II. Film and the senses. The third tendency in cinema -- Sensational cinema -- The experience of colour -- Notes on cinematic space -- Part III. Film, anthropology and the documentary tradition. Observation in the cinema -- Anthropology and the cinematic imagination -- Anthropological filmmaking : an empirical art -- Documentary and its doubles.
Includes bibliographical references (pages 190-192), filmography (pages 193-200) and index.
Keywords: Documentary films -- History and criticism